PENERAPAN KOMPRES NORMAL SALIN 0,9% TERHADAP KEJADIAN PLEBITIS DI RUMAH SAKIT TK. III 04.06.02 BHAKTI WIRA TAMTAMA SEMARANG - Ainnur Rahmanti; Grenada Nabela P (Jurnal Kesehatan Medika Udayana, 2018)
Phlebitis is inflammation that occurs in the endothelial wall in the tunic intima caused by mechanical and chemical irritation from the administration of infusion therapy. Compress using normal salin liquid 0.9% can improve the anti-inflammatory response and can facilitate the flow of blood circulation to the area of ??phlebitis injury so that it can accelerate wound healing. The purpose of this case study is to analyze the application of compresses using normal salin liquid 0.9% to the incidence of phlebitis in the Hospital grade III 04.06.02 Bhakti Wira Tamtama Semarang. This type of case study design belongs to a descriptive study using a case study approach method. The subjects in this case study used two patients who were infused and had phlebitis marks VIP scores degree of phlebitis 1-4. Analysis of the degree of phlebitis experienced was carried out by observation and measured through assessment of degrees using VIP Score (Visual Infusion Score) which is a score of 0-5. The compression using normal salin liquid 0.9% in phlebitis patients were for 2 days, for each day compress 3 times, in 1 time compress for 30 minutes. The results of the case studies were found in subjects I and subject II, each of the VIP scores of the degree of phlebitis 3 (erythema, pain, swelling along the cannula), each VIP score of phlebitis 0 (no phlebitis). It is suggested to Hospital grade III 04.06.02 Bhakti Wira Tamtama Semarang to be taken into consideration in nursing care interventions in the handling of nonpharmacological phlebitis so that no further complications occur.